A Holistic Framework for Planning and Managing Tropical Forest Resources - Milioli Mandal; Maalavika Ramu (Journal of Selvicoltura Asean, 2024)
Tropical forests are critical to global biodiversity and climate regulation, yet they face significant threats from deforestation, climate change, and unsustainable practices. Current management approaches often address these challenges in collaboration, leading to fragmented and effective strategies. This study aims to develop a holistic framework for planning and managing tropical forest resources. The goal is to integrate ecological, social, and economic dimensions to create a comprehensive strategy that enhances forest conservation and sustainable utilization. The research employs a mixed-methods approach, combining qualitative and quantitative data collection. A comprehensive literature review was conducted to identify existing frameworks and gaps. Case studies from tropical regions, including the Amazon, Southeast Asia, and Central Africa, were analyzed. Surveys and interviews with forest managers, local communities, and policymakers provided additional insights. The findings reveal that integrated management approaches considering ecological, social, and economic factors are more effective in achieving sustainable outcomes. Community-based Forest Management (CBFM) practices, supported by technological innovations and robust policy frameworks, significantly enhance forest conservation and utilization. Case studies demonstrate the practical application and benefits of a holistic management approach. A holistic framework for tropical forest management that integrates conservation and utilization strategies is essential for sustaining biodiversity and supporting local communities. The study highlights the importance of community engagement, technological advancements, and supportive policies. Future research should focus on refining this framework and addressing region-specific challenges to ensure its broad applicability and effectiveness.